The Alcohol Use Disorders Identification Test‐Consumption (AUDIT‐C) in the Assessment of Alcohol Use Disorders Among Acute Injury Patients. (22nd August 2013) - Wade, Darryl; Varker, Tracey; Forbes, David; O'Donnell, Meaghan
<x xml:space="preserve">Abstract</x> Background The Alcohol Use Disorders Identification Test‐Consumption (AUDIT‐C) is a brief alcohol screening test and a candidate for inclusion in recommended screening and brief intervention protocols for acute injury patients. The objective of the current study was to examine the performance of the AUDIT‐C to risk stratify injury patients with regard to their probability of having an alcohol use disorder. Methods Participants (n = 1, 004) were from a multisite Australian acute injury study. Stratum‐specific likelihood ratio (SSLR) analysis was used to examine the performance of previously recommended AUDIT‐C risk zones based on a dichotomous cut‐point (0 to 3, 4 to 12) and risk zones derived from SSLR analysis to estimate the probability of a current alcohol use disorder. Results Almost a quarter (23%) of patients met criteria for a current alcohol use disorder. SSLR analysis identified multiple AUDIT‐C risk zones (0 to 3, 4 to 5, 6, 7 to 8, 9 to 12) with a wide range of posttest probabilities of alcohol use disorder, from 5 to 68%. The area under receiver operating characteristic curve (AUROC) score was 0.82 for the derived AUDIT‐C zones and 0.70 for the recommended AUDIT‐C zones. A comparison between AUROCs revealed that overall the derived zones performed significantly better than the recommended zones in being able to discriminate between patients with and without alcohol use disorder. Conclusions The findings of SSLR analysis can be used to improve estimates of the probability of alcohol use disorder in acute injury patients based on AUDIT‐C scores. In turn, this information can inform clinical interventions and the development of screening and intervention protocols in a range of settings.